2014
DOI: 10.1182/blood-2014-01-551473
|View full text |Cite
|
Sign up to set email alerts
|

Two independent killing mechanisms of Candida albicans by human neutrophils: evidence from innate immunity defects

Abstract: Key Points Human neutrophils use 2 independent mechanisms for the killing of unopsonized and serum-opsonized C albicans. Unopsonized Candida killing depends on CR3 and CARD9 but not dectin-1; opsonized Candida killing on FcγR, PKC, and NADPH oxidase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
152
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(168 citation statements)
references
References 42 publications
9
152
0
2
Order By: Relevance
“…32 CLRs induce signaling and ROS formation via the NADPH oxidase system, which result in neutrophilmediated killing of C. albicans. 33 Our results showed that neutrophils also killed C. glabrata through an augmented respiratory burst (Fig. 2).…”
Section: Discussionmentioning
confidence: 71%
“…32 CLRs induce signaling and ROS formation via the NADPH oxidase system, which result in neutrophilmediated killing of C. albicans. 33 Our results showed that neutrophils also killed C. glabrata through an augmented respiratory burst (Fig. 2).…”
Section: Discussionmentioning
confidence: 71%
“…Neutrophils contribute to the initial steps of fungal killing, which plays a special role in neutropenic and immunosuppressed populations (36,45). CARD9 signaling and ROS formation by the NADPH oxidase system were involved in neutrophil killing of C. albicans (46). CR3 and the Dectin-1 receptor have been reported to be able to recognize cell wall ␤-glucan of C. albicans and mediate killing (46).…”
Section: Discussionmentioning
confidence: 99%
“…Fungi are recognized via PRRs, particularly C-type-lectin receptors (CLRs), Toll-like receptors (TLRs), and complement receptor 3 (CR3) (7)(8)(9). TLR signaling appears redundant for human antifungal host defense, as patients with myeloid differentiation primary response 88 (MYD88) and interleukin-1 receptor-associated kinase 4 (IRAK4) mutations develop pyogenic bacterial but not fungal infections (10).…”
Section: Introductionmentioning
confidence: 99%